Unsur Mistik dalam Upacara Pernikahan Adat Jawa di Medan Tembung: Analisis Perspektif Al-Qur’an - Syahputri, Fadhillah; Harahap, Syahrin (Kartika: Jurnal Studi Keislaman, 2025)
This study examines mystical elements in Javanese traditional wedding ceremonies in Medan Tembung through the perspective of Qur’anic studies. Javanese wedding traditions consist of various stages rich in cultural and spiritual values, including mystical elements that are still preserved by the local community. The objective of this research is to analyze the forms of mystical elements embedded in the wedding rituals and to assess their conformity with Islamic teachings based on the Qur’an. This research employs a qualitative approach using literature review and field observation methods. The findings reveal that several rituals, such as determining auspicious days (weton and primbon), preparation rituals (siraman, offerings, suwuk, and tarub), bridal make-up (paes and attire), as well as the panggih ceremony (egg stepping and tepung tawar), contain mystical elements believed to influence married life. From the perspective of the Qur’an, these practices can be categorized into two: acceptable practices that do not contradict the principle of tawhid, such as prayers or cultural symbolizations, and practices that conflict with Islamic faith as they involve belief in powers other than Allah. This study emphasizes the need for a critical and educational approach based on Qur’anic interpretation to harmonize cultural traditions with Islamic teachings while preserving the aesthetic and cultural richness of Javanese heritage.